Archaeological marine carbonates in northern Hokkaido, Japan: methodology, chronology and palaeothermometry - Branscombe, T (2022)
The site of Hamanaka 2, Rebun Island (Hokkaido), contains an archaeological record including well-preserved faunal remains, including clam shells and cod otoliths, from hunter-gatherer groups across the Epi-Jomon to Historical Ainu periods. As demonstrated by sclerochronologists worldwide, incremental stable isotope analysis of marine carbonates can provide an archaeologically-relevant and directly-datable proxy record of oceanic palaeotemperature, which is especially important for coastal sites such as Hamanaka 2. Despite this, marine carbonates from the site have not yet been used for this purpose, partly due to concerns over a variable regional marine reservoir effect. This, in combination with the possibility of ‘old’ shells being incorporated into younger stratigraphic units, means that any climatic information gained can be difficult to associate conclusively with the stratigraphic unit from which it was excavated. This thesis aims to address the methodological and interpretational obstacles relating to the archaeological use of this material at Hamanaka 2, and considers the local palaeotemperature record these materials can provide and their implications.